Experimental Validation of Novel Glypican 3 Exosomes for the Detection of Hepatocellular Carcinoma in Liver Cirrhosis - Aydin Y; Koksal AR; Thevenot P; Chava S; Heidari Z; Lin D; Sandow T; Moroz K; Parsi MA; Scott J; Cohen A; Dash S (Journal of Hepatocellular Carcinoma, 2021)
Yucel Aydin,1 Ali Riza Koksal,1,2 Paul Thevenot,3 Srinivas Chava,1 Zahra Heidari,4 Dong Lin,1 Tyler Sandow,5 Krzysztof Moroz,1 Mansour A Parsi,2 John Scott,1 Ari Cohen,3,6 Srikanta Dash1,7 1Department of Pathology and Laboratory Medicine, Tulane University Health Sciences Center, New Orleans, LA, USA; 2Department of Gastroenterology and Hepatology, Tulane University Health Sciences Center, New Orleans, LA, USA; 3Institute of Translational Research, Ochsner Health, New Orleans, LA, USA; 4Chemical and Biomedical Engineering, Tulane University, New Orleans, LA, USA; 5Department of Radiology, Institute of Translational Research, Ochsner Health, New Orleans, LA, USA; 6Multi-Organ Transplant Institute, Ochsner Health, New Orleans, LA, USA; 7Southeast Louisiana Veterans Health Care System, New Orleans, LA, USACorrespondence: Srikanta Dash Email sdash@tulane.eduBackground and Aims: Hepatocellular carcinoma (HCC) developing in the context of preexisting cirrhosis is characterized by impaired autophagy that results in increased exosome release. This study was conducted to determine whether circulating exosomes expressing glypican 3 (GPC3) could be utilized as a biomarker for HCC detection and treatment response in patients with cirrhosis.Methods: Immunohistochemistry was performed to assess p62 and GPC3 expression in the lesion and adjacent tissue from cirrhosis with HCC. GPC3-enriched exosomes were captured by an enzyme-linked immunosorbent assay (ELISA). The diagnostic specificity of serum exosome-derived GPC3 (eGPC3) was determined using samples obtained from malignancy-free controls, malignancy-free cirrhotics, cirrhotics with confirmed HCC, and patients with a non-HCC malignancy. The performance of eGPC3 was validated using serum samples of HCC patients received chemotherapy.Results: We found that the expression of p62 and GPC3 was significantly increased in HCC tissues compared to adjacent cirrhotic liver. Impaired autophagy and exosome shedding were confirmed in HCC cell lines. Mass spectroscopic analysis revealed that GPC3 was enriched in exosomes isolated from HCC cell lines. An affinity ELISA assay was developed that specifically captures GPC3 positive exosomes in the serum. Total exosome concentration and eGPC3 were significantly elevated in cirrhotic patients with HCC as compared to the reference control groups. Furthermore, decreases in post-treatment exosome concentration and eGPC3 levels were more closely correlated with response to locoregional chemotherapy compared to change in serum AFP in HCC patients awaiting liver transplantation.Conclusion: We developed an affinity exosome capture assay to detect GPC3 enriched exosomes. Our preliminary assessment shows that GPC3 positive exosomes can be used for HCC detection and prediction of treatment outcomes.Keywords: hepatocellular carcinoma, autophagy, exosome, glypican 3, surveillance